"How does my family affect me?" The family cultural capital impact on Chinese junior high school students' academic achievement. (December 2022) - Yu, Shuo; Liu, Ying; Guo, Rui
Highlights: Three kinds of family cultural capitals have a positive impact on students' academic achievement. Family cultural capital plays a mediating role between family socioeconomic status and academic achievement. Parental involvement affects the academic achievement of junior high school students. Learning attitude plays as a mediating variable of family objectified cultural capital. Self-education expectations functions as a mediating variable of family embodied cultural capital. Abstract: Family cultural capital plays an increasingly obvious role in students' academic achievement. This study mainly analyzes family cultural capital's influence on junior high school students' academic achievement. Based on regression analysis and mesomeric effect analysis, we found the family institutionalized cultural capital, family specific cultural capital, and family objectified cultural capital have positive influence on the academic achievement of junior high school students. Parent participation plays as a mediator of family institutionalized cultural capital. Learning attitude functions as a mediator of family's objectification cultural capital. Self-education expectation works as a mediator of family specific cultural capital. All these three factors affect junior high school students' academic achievement obviously. Therefore, the academic achievement of junior high school students can not only be improved by increasing the family cultural capital, but also by enhancing parent support for academic participation, raising educational expectations for students' development, and cultivating students' good learning attitudes.